Aplikasi Metode Grey Forecasting Pada Peramalan Kebutuhan Bahan Bakar Alternatif Ramah Lingkungan di PT. Indocement Tunggal Prakarsa Tbk - Nariswari, Nanda Lokita; Rosyidi, Cucuk Nur (Performa: Media Ilmiah Teknik Industri, 2015)
Forecasting is one of the methods required by a company to plan the demand of raw materials in the future, in order to avoid the emergence of various problems such as stock out. However, not all forecasting methods can be used to forecast demand in the short term a specially a condition where the company only has a few historical data. Grey method is a forecasting method which can be used to predict the short-term demand. The purpose of this study is to determine how well the Grey method used to predict the demand of alternative energy and compared with other forecasting methods. Mean Squared Error (MSE) is used as a measure of the goodness of the method. The result of the study indicates that the Grey Forecasting Methods MSE value that is smaller than other time series forecasting methods.